Epilepsy during pregnancy: focus on management strategies - Borgelt LM; Hart FM; Bainbridge JL (Dove Medical Press, 2016)
Laura M Borgelt,1 Felecia M Hart,2 Jacquelyn L Bainbridge2 1Departments of Clinical Pharmacy and Family Medicine, 2Departments of Clinical Pharmacy and Neurology, University of Colorado Anschutz Medical Campus, Skaggs School of Pharmacy and Pharmaceutical Sciences, Aurora, CO, USA Abstract: In the US, more than one million women with epilepsy are of childbearing age and have over 20,000 babies each year. Patients with epilepsy who become pregnant are at risk of complications, including changes in seizure frequency, maternal morbidity and mortality, and congenital anomalies due to antiepileptic drug exposure. Appropriate management of epilepsy during pregnancy may involve frequent monitoring of antiepileptic drug serum concentrations, potential preconception switching of antiepileptic medications, making dose adjustments, minimizing peak drug concentration with more frequent dosing, and avoiding potentially teratogenic medications. Ideally, preconception planning will be done to minimize risks to both the mother and fetus during pregnancy. It is important to recognize benefits and risks of current and emerging therapies, especially with revised pregnancy labeling in prescription drug product information. This review will outline risks for epilepsy during pregnancy, review various recommendations from leading organizations, and provide an evidence-based approach for managing patients with epilepsy before, during, and after pregnancy. Keywords: epilepsy, teratogens, anticonvulsants, medication therapy management